Applications of Modern Technologies in the Production of Aircraft Propeller Prototype - Marek Bistak; Stefan Medvecky; Eva Gajdosova; Marian Dzimko; Stanislav Gramblicka; Robert Kohar; Marian Stopka; Jan Steininger; Slavomir Hrcek; Michal Tropp; Frantisek Brumercik (Communications - Scientific letters of the University of Zilina, 2017)
In the field of engineering relatively new designs and manufacturing processes are constantly emerging. These changes are often seen in designing and manufacturing of prototypes or in single part production. We decided to analyse an aircraft propeller prototype using modern technologies. Existing aircraft blade design was converted to digital models which were analysed.